The Impact of Habituation of Spiritual Activities on Social Attitudes and Behaviors of Observational Study Students at SD Muhammadiyah 3 Bandung - Mulyani, Yani; Muyassar M, Raihan; Sholiehah, Nurul; Hadiantini, Dian; Rahmawati, Eti; Supala (Yayasan Mentari Madani, 2025)
The formation of social attitudes and behaviors among elementary school students requires sustainable and contextual character education strategies. One approach widely implemented in faith-based schools is the habituation of spiritual activities through daily religious routines. This study aims to describe the impact of habituated spiritual activities on students’ attitudes and social behaviors at SD Muhammadiyah 3 Bandung. The study employed a descriptive qualitative approach with an observational study design. Data were collected through participatory observation of students’ spiritual activities and documentation, including activity schedules, school regulations, and archives of religious programs. Data analysis was conducted thematically through data reduction, data display, and conclusion drawing. The findings indicate that the habituation of spiritual activities such as prayers before and after lessons, BTQ/Khas programs, muroja’ah, congregational Dhuha prayer, congregational Zuhur prayer, Qur’anic memorization (tahfidz AlQur’an), and the implementation of the 6S culture (Smile, Greeting, Salutation, Addressing, Politeness, and Courtesy) contributes positively to the development of students’ discipline, responsibility, and prosocial behavior. Scheduled worship routines encourage punctuality, compliance with rules, and more orderly social interactions among students. However, observational findings also suggest that the impact of spiritual habituation is not always linear in relation to students’ engagement in academic learning. Therefore, proportional management and continuous evaluation of spiritual habituation programs are necessary to ensure that character development benefits remain balanced with students’ academic learning needs. Keywords: spiritual habituation, social behavior, elementary school, student attitudes, observational study